PENERAPAN SANKSI DENDA TILANG BAGI PELANGGAR LALU LINTAS BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Halawa, Sona Seki; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In Law No. 22 of 2009 on Road Traffic and Transport has strictly regulated the way the use of the vehicle must comply with the rules that have been specified, but in reality there are often encountered people who use vehicles not based on existing regulations. The provisions concerning the application of penalties against any violators ticketed and lintassecara has clearly stipulated in the law. Problems drawn from this paper is the application of financial penalties First How ticketed for traffic violators based on Law Number 22 Year 2009 regarding traffic and road transport in the jurisdiction in Pekanbaru City Police?, Second What are the obstacles faced in the implementation of sanctions speeding ticket fines for traffic violations based on law Number 22 Year 2009 regarding traffic and road transport in the jurisdiction in Pekanbaru City Police Third ?, How dilakukakan efforts to overcome the obstacles that arise in the application of sanctions for violators of traffic ticket fines based on the law law Number 22 Year 2009 on road traffic and transportation in the jurisdiction of City Police Pekanbaru? This type of research can be classified this type of research legal sociology, because law research in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem was conducted on the examined. This research is done law Pekanbaru City Police, collection techniques in this study with interview, questionnaire, and the study of literature. First application of penalties for violation traffic ticket based on Law Number 22 Year 2009 on Road Traffic and Transportation apparently this has not been effective in the show from a number of traffic violations that are still high. The second obstacle in the application of financial penalties ticketed ineffective implementation of the speeding ticket fines indicate that the number of speeding ticket fines are still in the low category, causing no deterrent effect to traffic violators. Third attempt to overcome the high level of traffic violations in the jurisdiction of the Pekanbaru City Police conduct counseling on the importance of traffic rules to the public. My advice to the need to increase public awareness of the law and the application of tougher sanctions, especially regarding Traffic regulations.